Propolis anti-inflammatory effects on MAGE-1 and retinoic acid-treated dendritic cells and on Th1 and T regulatory cells - Santiago, Karina Basso [UNESP]; Conti, Bruno Jose [UNESP]; Cardoso, Eliza de Oliveira [UNESP]; Conte, Fernanda Lopes [UNESP]; Tasca, Karen Ingrid [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Golim, Marjorie de Assis [UNESP]; Cruz, Maria Tereza; Sforcin, Jose Mauricio [UNESP] (Cevap-sao Paulo State Univ-unesp, 2023)
Background: Propolis exhibits huge potential in the pharmaceutical industry. In the present study, its effects were investigated on dendritic cells (DCs) stimulated with a tumor antigen (MAGE-1) and retinoic acid (RA) and on T lymphocytes to observe a possible differential activation of T lymphocytes, driving preferentially to Th1 or Treg cells.Methods: Cell viability, lymphocyte proliferation, gene expression (T-bet and FoxP3), and cytokine production by DCs (TNF-alpha, IL-10, IL-6 and IL-1 beta) and lymphocytes (IFN-gamma and TGF-beta) were analyzed.Results: MAGE-1 and RA alone or in combination with propolis inhibited TNF-alpha production and induced a higher lymphoproliferation compared to control, while MAGE-1 + propolis induced IL-6 production. Propolis in combination with RA induced FoxP3 expression. MAGE-1 induced IFN-gamma production while propolis inhibited it, returning to basal levels. RA inhibited TGF-beta production, what was counteracted by propolis.Conclusion: Propolis affected immunological parameters inhibiting pro-inflammatory cytokines and favoring the regulatory profile, opening perspectives for the control of inflammatory conditions.
Keywords: Dendritic cells; T CD4+cells; MAGE-1; Retinoic acid; Propolis; Immunomodulation